Turkey Green Growth Policy Paper : Towards a Greener Economy - World Bank (Washington, DC, 2013)
The report is organized in seven chapters. Following the introductory chapter, chapter two sets the stage by reviewing the structure of Turkey's economy and its performance, as well as the challenges and opportunities provided by Turkey's current growth path from implementing a 'green agenda' linked to achieving standards set by European Union (EU) Directives and Organization for Economic Cooperation and Development (OECD) principles; this is followed by a review of where Turkey stands compared to developed and emerging economies, in terms of what is broadly understood as a comprehensive approach to green growth. Chapter three uses a narrower, more operational, definition of green growth for the purposes of the analysis undertaken in the policy note. Chapter four presents an assessment of the seven strategic sectors selected for a more focused analysis. It also highlights the greening potential within these sectors. Chapter five reviews the range of policy instruments available in the European Union (EU) and other emerging international experiences, as well as the relevance of these policy options to the objectives of the policy note. Chapter six presents the economy-wide framework and the results of the pilot economic 'impact analysis' of two types of greening scenarios: an urban scenario (linked to production and consumption by firms and households) and a rural scenario focused on agriculture. Finally, chapter seven concludes with an initial set of recommendations.